Antimicrobial activity of ethyl acetate extracts of Streptomyces sp. CRB46 and the prediction of their bioactive compounds chemical structure - Ambarwati Ambarwati; Subagus Wahyuono; Sukarti Moeljopawiro; Triwibowo Yuwono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ambarwati A, Wahyuono S, Moeljopawiro S, Yuwono T. 2020. Antimicrobial activity of ethyl acetate extracts of Streptomyces sp. CRB46 and the prediction of their bioactive compounds chemical structure. Biodiversitas 21: 3380-3390. The goal of the research was to determine the antimicrobial activity of ethyl acetate extracts of Streptomyces sp. CRB46 and predict their chemical structure of the bioactive compounds based on the AntiSMASH analysis of the whole genome sequencing. Streptomyces sp. CRB46 was isolated from Cyperus rotundus L. rhizosphere in the Cemoro Sewu highland, Indonesia (1920 meters above sea level). The results showed that the supernatant ethyl acetate (EAS) extract could inhibit 11 of 12 tested microorganisms with a diameter of the inhibition zone ranging from 17-35 mm (paper disc method). The supernatant extract was found more effective in inhibiting microorganisms than the ethyl acetate extract of pellets (EAP). The EAP extract was only able to inhibit the growth of seven tested microorganisms (16-26 mm). The results of LCMS analysis showed that crude extract of EAS consisted of 20 mixtures of organic compounds. Based on FTIR analysis, 16 functional groups were found in the EAS extracts. In addition, based on AntiSMASH analysis, it was also found that Streptomyces sp. CRB46 produced eight classes of bioactive compounds, but only six compounds have been identified as their chemical structures. It can, therefore, be concluded that Streptomyces sp. CRB46 has the potential to produce bioactive compounds that can be used for microbial infection treatment.